Optimisation and validation of a specific analytical method for the determination of thiram residues in fruits and vegetables by LC–MS/MS - Peruga, Aranzazu; Grimalt, Susana; López, Francisco J.; Sancho, Juan V.; Hernández, Félix (Food chemistry, 2012)
► Specific analytical methodology is developed for determination of dithiocarbamate fungicide thiram in fruits and vegetables. ► The method is based on LC coupled to tandem MS. ► Thiram degradation along sample treatment is minimised, adding specific reagents and operating at around 5°C. ► The excellent sensitivity and selectivity of the method allows monitoring for compliance of MRLs, with LOQ of 0.01mg/kg. ► The acquisition of several SRM transitions allows the reliable confirmation of thiram in the samples at very low levels. Thiram is a non-systemic dithiocarbamate fungicide, which is easily degraded during sample preparation since it is affected by pH, matrix components and temperature. In this work, specific methodology for thiram analysis in vegetable (eggplant and lettuce) and fruit (strawberry) samples has been developed based on liquid chromatography coupled to tandem mass spectrometry (LC–MS/MS). Minimising thiram degradation during standards storage and sample preparation was carefully studied. The effect of low temperature (about 5°C), addition of a dehydrating agent (Na2SO4 anhydrous), pH regulator (NaHCO3), and enzymatic activity reduction (EDTA) during extraction was evaluated. The optimised procedure was validated for eggplants, lettuces, and strawberries. Satisfactory recoveries, between 80% and 106%, and relative standard deviations below 10% were obtained at 0.1 and 0.01mg/kg fortification levels (n=5). Limits of detection below 0.0012mg/kg were achieved. The validated method has been applied to eggplant and lettuce samples collected from different field trials as well as several strawberry and apple samples.